Drug and therapeutics committees in Jordanian hospitals: a nation-wide survey of organization, activities, and drug selection procedures - Alefan Q; Alshareef S; Al-Shatnawi S (Pharmacy Practice, 2019)
Background: Drug and Therapeutics Committees (DTCs) were founded about a century ago as a guide for dealing with drugs in hospitals. Since then, it has shown a vital role in rational drug use in terms of regulatory and educational activities. Objective: To describe structures, functions, and activities of hospital DTCs. Methods: A questionnaire was developed based on previous studies. Questions consisted of information on respondents’ demographics; structures, functions, and activities of DTCs; drug selection process and resources used, and factors and criteria used in drug selection. Results: The overall response rate was 95%. DTCs were mainly present in most large hospitals (45%). All DTCs had hospital pharmacists in their structure and most of them (66%) met monthly. The main responsibilities of DTCs were related to general prescribing policies. The number, frequency, and severity of adverse drug reactions were the most reported criteria for the drug selection process. Legal implications for practical, economic, and organizational factors were the most important factors that were reported for drug selection. Conclusions: DTCs are mainly present in most large hospitals. The main responsibilities of the DTC in Jordanian hospitals are general prescribing policies, drug selection, hospital formulary editing, and reporting of ADR to external authorities.